Study on Durability of Composite Marine Structure using FEA - Zainudin, Mohamad Firdaus; Tajul Arifin, Ahmad Mubarak (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Marine structures are subjected to a wide variety of loads that are cyclic in nature (e.g., storm winds, waves, and currents). The marine environment presents the biggest difficulty to researchers in terms of selecting a suitable material for structural purposes. The durability behavior of composite structures that can be encountered in marine structure is investigated here in this research. Through the use of FEA, the goal of this study is to identify the composite structure used in marine application and to investigate the behavior characteristic of composite structures in terms of impact test and flexural test. The Charpy impact test and three-point bending test were all carried out with the assistance of ANSYS Workbench. As reinforcing materials, chopped strand mat (CSM) and woven roving (WR) fabric were used for the research, and epoxy resin was used in a stacking sequence of [CSM/0/90/CSM]2s. Other materials used in the research were as follows: The simulation carried out with ANSYS allowed for the determination of the stress, strain, deformation, force, and energy absorption, all of which were based on the outcome. Based on the simulation results for [CSM/0/90/CSM]2s, the energy recorded during the impact test is 0.282 J and the peak load of 738N. In bending test simulation, the bending stress for [CSM/0/90/CSM]2s is 633.43 MPa. In addition, more different test is recommended for future work.